Monetary policy and the exchange rate in Norway - Mathis Mæhlum (Norges Bank, 2025)
I estimate how monetary policy affects the exchange rate in Norway using a local projection instrumental variables (LP-IV) framework with high-frequency monetary policy surprises as instruments. I find that a surprise increase in the Norwegian policy interest rate leads to an immediate appreciation of the currency followed by a gradual depreciation. The effects are short-lived, with the exchange rate returning to its pre-shock level within three months. Surprise changes in monetary policy in the Euro zone has a similar, but opposite effect on the Euro/NOK exchange rate. Increases in the projected interest rate path published by Norges Bank also appreciates the currency, and the effects are stronger for changes at longer projection horizons.
hdl:11250/3192045
Keywords: C26; E43; E44; E52; E58; F31; F42; 330; Monetary Policy Transmission; Exchange Rate; Interest Rates; High Frequency